Tilting high-intensity focused ultrasound phased array to augment the focal steering range for treatment of uterine fibroids. (September 2020) - Li, Ke; Chen, Yini; Xu, Yanjun; Bai, Jingfeng; Chen, Yazhu; Ji, Xiang
Abstract: Phased arrays are increasingly employed in clinical high-intensity focused ultrasound (HIFU) systems for treatment of uterine fibroids. However, the electronic steering range of current phased arrays is insufficient to cover a symptomatic uterine fibroid. This study proposes a method to augment the focal steering range for HIFU treatment of uterine fibroids. Geometric focus can be shifted by tilting HIFU phased array around two orthogonal axes with a rotating platform, and both rotating angles can be adjusted up to 15° with tilt radius of 277 mm according to the shift of geometric focus. A three-layer (skin, fat and muscle) tissue model was used as the beam propagation path. The acoustic fields with and without tilting HIFU phased array were characterized by numerical simulation and hydrophone measurement. Focal accuracy was evaluated in phantoms and targeting areas were ablated in in vivo pigs' thighs. In combination with the electronic focal steering, the steering range in the focal plane has been augmented to ±53 mm from ±6 mm. In the phantoms, the mean focal error has been increased from 0.2 mm to 0.9 mm with the geometric focus shift ranged from 10 mm to 40 mm. In vivo experimental results have proved that it is safe and effective to ablate the 25 mm × 25 mm square area. Tilting the HIFU phased array is feasible to safely augment the focal steering range, which can potentially improve the efficacy of HIFU treatment.